Immuncontraception Reversibility Test of Goat Zona Pellucida-3 (gZP3) on Mice (Mus musculus) - IMAM MUSTOFA (HAYATI Journal of Biosciences, 2006)
The aim of this study was to prove the reversibility of gZP3 protein on mice as an animal model. Treatment group of mice (Mus musculus) were immunized with 40 ug goat zona pellucida-3 (gZP3) as an anti fertility agent. Control group of mice were injected only with physiologic solution. The mice were injected three times, the first injection as an immunization. The second and third injected as a booster with 14 days interval. The first injection, gZP3 suspension was diluted in complete Freund’s adjuvant (CFA). The boosters, gZP3 suspension was diluted in incomplete Freund’s adjuvant (IFA) 1:1 (v/v). Blood samples were collected before immunization, seven days after the second booster and at the time of parturition. Seven days after the last injection, the mice were mated, and the parturition was observed after that. The result showed that antibody titer of immunized mice serum was increasing (P < 0.05) seven days after immunization, and decreasing (P > 0.05) after parturition compared to antibody titer of serum before immunization. Dot blotting analysis showed that gZP3 protein could recognize gZP3 antibody of the immunized mice. Protein of gZP3 as an immunocontraceptive substance was reversible in 91.60 + 4.90 days. This reversibility was longer (P < 0.05) compared to control mice i.e. 26.50 + 4.30 days. Key words: immunocontraception, goat zona pellucida-3, reversibility, mice, animal model, gZP3 antibody